2010
DOI: 10.1089/jmf.2009.0099
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Activity of Aqueous Extract of Bowdichia virgilioides in Mice

Abstract: Bowdichia virgilioides Kunth (Family Fabaceae) is a plant that is distributed widely in the tropical and subtropical regions of the world. In the northeast region of Brazil, where B. virgilioides is called "sucupira-preta," the stem bark is used in folk medicine to treatment of inflammatory and painful diseases. This study aimed to evaluate the antinociceptive activity of the aqueous extract of the dried stem bark of B. virgilioides. The aqueous extract of B. virgilioides in doses of 50, 100, 200, and 400 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Confirming the pharmacological potential of the extracts from this plant, we and other authors have previously demonstrated that extracts from its bark and leaves are able to alleviate painful and inflammatory conditions in experimental models (Barros et al, 2010;Silva et al, 2010;Thomazzi et al, 2010). Indeed, these pharmacological effects are related to natural phytochemical constituents present in the extracts.…”
Section: Discussionsupporting
confidence: 67%
“…Confirming the pharmacological potential of the extracts from this plant, we and other authors have previously demonstrated that extracts from its bark and leaves are able to alleviate painful and inflammatory conditions in experimental models (Barros et al, 2010;Silva et al, 2010;Thomazzi et al, 2010). Indeed, these pharmacological effects are related to natural phytochemical constituents present in the extracts.…”
Section: Discussionsupporting
confidence: 67%
“…Although S. convoluta is widely used in the folk medicine in the semi-arid region of Brazil, no report about the antinociceptive activity of this plant is recorded in the literature. The study of plant species that traditionally have been used for the relief of the pain should still be seen as a logical research strategy in the search for new analgesic drugs [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory and antinoceptive potential (Thomazzia et al, 2010;Silva et al, 2010;Barros et al, 2010) Cardiotonic, sedative and hypoglycemic activities (Aragão et al, 2010;Consolini et al, 2006;) Rheumatism and renal colic (Rodrigues & Carvalho, 2001) Diarrhoea, dysentery, intestinal colic, cystitis, antiviral activity and inhibition of 5-lipoxygenase (Cecílio et al, 2012;Lorenzi & Matos, 2002;Braga et al, 2000;Panizza, 1997) Antidiarrheal, gastro-protective and cicatrising activities (Orsi et al, 2012) Jacaranda species are used for blenorrhagy, skin ulcers, anti-syphilis and anti-gonorrhoea, and anti-inflammatory remedies (Gachet & Schühly, 2009) Struthanthus species are used in parasitosis and skin disorders (Martinez & Barboza, 2010) Wound-healing, anti-inflammatory, anti-ulcerogenic, anti-tyrosinase and Molluscicidal activities (Lopes et. al, 2005;Rebecca et al, 2003;Baurin et al, 2002;Bezerra et al, 2002) Antimalarial, anticancer, hypoglycaemic (Masaba, 2000;Izevbigie et al, 2008) FeCl3 (0.1%).…”
Section: Medicinal Usesmentioning
confidence: 99%